Dampak Digitalisasi terhadap Inovasi Teknologi pada Usaha Mikro, Kecil, dan Menengah - Mohamad Chaidir; Grace Yulianti; Seger Santoso (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to examine the impact of digitalization on technological innovation in Micro, Small, and Medium Enterprises (MSMEs) through a qualitative literature review approach. In the era of digital transformation, MSMEs face various opportunities and challenges. Digitalization has the potential to enhance MSMEs' competitiveness by accelerating product, service, and business process innovation, but it also requires them to overcome limitations such as limited technological skills and financial constraints. By analyzing previous studies using the bivariate probit model, this study finds that digital technology adoption is positively correlated with increased innovation in MSMEs. Digitalization has been shown to expand market access, improve operational efficiency, and strengthen MSMEs' adaptability to changes in the business environment. However, internal and external barriers, such as low digital literacy and limited funding access, remain significant obstacles. This study emphasizes the importance of support from the government and related institutions in providing training and funding access so that MSMEs can fully leverage digitalization for sustainable innovation.